A Comprehensive Education and Prevention Program for Student-Athletes: A Life Skills/Experiential Learning Model - Hale, Bruce D.; Waalkes, Deanna M.; Kenepp, Diana L.; Lynch, James M.; Bennell, David L.; Wang, MinQi (My University, 1994)
The purpose of this longitudinal drug prevention program sponsored by the NCAA was to provide a unique experiential learning approach for student-athletes. Data were obtained from freshman student-athletes before and after a fall semester drug education course via a questionnaire measuring self-esteem, knowledge, attitudes, frequency of usage, risk factors, and demographic variables. In this program, freshman student-athletes were required to enroll in a one-credit health education "Values and Health" course during the fall semester. Topics included stress management skills, sports nutrition, eating disorders, sexuality, date rape, and, most importantly, five session on alcohol use and abuse. The authors collecgted 158 freshman drug questionnaires prior to the start of the program, and collected 43 post-tests after the course for matched data. They also collected data from 33 senior track athletes. For a control group, they also surveyed 60 club sport athletes and 87 non-athletes. The data for all groups was the Student-Athlete Service Questionnaire which included questions from the Rosenberg Self-Esteem Scale. MANOVAs were computed for four dependent measures (self-esteem, knowledge, attitude, and risk factors) and independent variables (drug user/non-user, subject sex, sprot type, parental income cateogry, financial aid status, and time) were examined for each drug category. The effectiveness of the freshman program was analyzed, and further comparisons were made with other student-athlete and non-athlete groups. Alcohol was found to be the most widely used drug, while use of performance and societal drugs was extremely low. The freshman program was found to have a significant impact on enhancing drug knowledge, as findings indicated freshman athletes (especially in non-contact sports) are at a higher risk for recreational drug use than other athletes and non-athletes. Additional multivariate analyses examined other attitudinal and psychological variables.
Keywords: drugs/alcohol